2019
DOI: 10.7717/peerj.7627
|View full text |Cite
|
Sign up to set email alerts
|

Dendrobium alkaloids decrease Aβ by regulating α- and β-secretases in hippocampal neurons of SD rats

Abstract: Background Alzheimer’s disease (AD) is the primary cause of dementia in the elderly. The imbalance between production and clearance of amyloid β (Aβ) is a very early, often initiating factor in AD. Dendrobium nobile Lindl. alkaloids (DNLA) extracted from a Chinese medicinal herb, which have been shown to have anti-aging effects, protected against neuronal impairment in vivo and in vitro. Moreover, we confirmed that DNLA can improve learning and memory function in elderly normal mice, indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…Investigation on the mechanisms underlying the neuroprotective effects of DNLA revealed that DNLA prominently improved the neurobehavioral performance and prevented LPS-induced elevation in tumor necrosis factor receptor one via inhibition of phosphorylated p38 mitogen-activated protein kinases and the downstream nuclear factor kappa-B signal pathway ( Li et al, 2011 ; Ng et al, 2012 ). Moreover, DNLA decreased the level of intracellular amyloid β peptide (Aβ) by improving impaired autolysosomal proteolysis in amyloid precursor protein/presenilin one mice ( Nie et al, 2018 ), and regulating α- and β-secretase in hippocampal neurons of Sprague-Dawley rats ( Huang J. et al, 2019 ). The reduction of Aβ attenuated Aβ 25–35 -induced spatial learning and memory impairments by increasing the protein expression of neurotrophic factors, such as brain-derived neurotrophic factor, ciliary neurotrophic factor, and glial cell line-derived neurotrophic factor ( Nie et al, 2016 ; Nie et al, 2018 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Investigation on the mechanisms underlying the neuroprotective effects of DNLA revealed that DNLA prominently improved the neurobehavioral performance and prevented LPS-induced elevation in tumor necrosis factor receptor one via inhibition of phosphorylated p38 mitogen-activated protein kinases and the downstream nuclear factor kappa-B signal pathway ( Li et al, 2011 ; Ng et al, 2012 ). Moreover, DNLA decreased the level of intracellular amyloid β peptide (Aβ) by improving impaired autolysosomal proteolysis in amyloid precursor protein/presenilin one mice ( Nie et al, 2018 ), and regulating α- and β-secretase in hippocampal neurons of Sprague-Dawley rats ( Huang J. et al, 2019 ). The reduction of Aβ attenuated Aβ 25–35 -induced spatial learning and memory impairments by increasing the protein expression of neurotrophic factors, such as brain-derived neurotrophic factor, ciliary neurotrophic factor, and glial cell line-derived neurotrophic factor ( Nie et al, 2016 ; Nie et al, 2018 ).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…DNLA was isolated from the extracts and analyzed by LC-MS/MS. Alkaloids accounted for 79.8% of the DNLA and were comprised of 92.6% dendrobine (C16H25O2N), 3.3% dendrobine-N-oxide (C16H25O3N), 2.0% nobilonine (C17H27O3N), 0.9% dendroxine (C17H25O3N), 0.32% 6-hydroxy-nobilonine (C17H27O4N), and 0.07% 13-hydroxy-14-oxodendrobine (C16H23O4N) [ 21 , 24 ]. A β 25–35 was purchased from Sigma (American).…”
Section: Methodsmentioning
confidence: 99%
“…Neurons were seeded into 96-well plates and treated with DNLA for 30 h at different concentrations. After five replicates were made for each treatment, cell viability was evaluated by MTT assays as previously described [ 24 ]. The cell viability is expressed as an OD percentage of cells with the indicated treatments in cells treated with the DMSO control treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…is a Chinese medicine for many disorders and Dendrobium Nobile Lindl. alkaloids (DNLA) has been shown to have protective effects against neurodegenerative diseases, such as to reduce the Aβ 25-35 -induced cytotoxicity and axonal degeneration in primary neurons [18,19], attenuate LPS-induced hyperphosphorylation of tau, Aβ-induced neuronal apoptosis and synaptic loss [20,21], reduce the formation and aggregation of toxic amyloid in SD rats [22], and also protect against aging-related learning and memory deficits, neuronal aging and loss in SAMP8 mice [23,24]. In addition, DNLA are effective in alleviating inflammation.…”
Section: Introductionmentioning
confidence: 99%